التقليل من التأثير البيئي لمنتجات الصحة النباتية - منار, العايب; ايناس, مصباحي; أسماء, ساري نصر; هناء, لوبيري; نور الهدى, نصرات (جامعة الشهيد حمه لخضر الوادي, 2023)
منتجات الصحة النباتية هي مستحضرات ومواد تحتوي على مواد فعالة ومهمة من أجل حماية النباتات من تأثيرات الكائنات الضارة أو تقوم بتثبيط عملها، تتكون المبيدات من محاليل أو مخاليط من مركبات نشطة على النباتات. وتعرف ايضا المنتجات الصحة النباتية بعدة مصطلحات مثل: المنتجات المضادة للطفيليات للاستخدام الزراعي، منتجات مكافحة أعداء المحاصيل، المنتجات الصيدلانية الزراعية والمنتجات الصيدلانية النباتية ومنتجات وقاية النبات والمنتجات الزراعية، تعرف المبيدات بأنها جزيئات صغيرة تتكون من جزء نشط وسام وجزء ثانوي يساعد على استقرار المبيد، للمبيدات عدة أنواع واستعمالات تساعد على ضمان المحاصيل وجودتها. ولكن لها آثار جانبية غير مرغوب فيها على البيئة، وكذلك تؤدي الملوثات بصفة عامة والمبيدات بصفة خاصة إلى تأثيرات ضارة على الدورة الحيوية بطرق مباشرة وغير مباشرة، سلطت العديد من الدراسات العلمية حول العالم الضوء على مخاطر التلوث المرتبط بمنتجات الصحة النباتية على البيئة والنظام البيئي، وقد تم إستخدام نماذج لتقييم المخاطر المرتبطة باستخدام المبيدات وكذلك تم استعمال طرق وتقنيات للكشف على مخلفاتها. وللتقليل من هذه المخاطر إقترحنا عدة حلول وبدائل أثبثت فعاليتها في خفض حدة تلوث البيئة بمنتجات الصحة النباتية أهمها دليل إستخدام هذه المنتجات الذي يمثل وقاية للمستخدم والبيئة، وإستخدام المبيدات الحيوية بدلا من المبيدات الكيميائية الضارة، وبرامج وإستراتيجيات تقليل الأثر الناجم عليها، وللمساهمة في هذا الخفض عرضنا أساليب مكافحة الآفات بطريقة بيئية سليمة. Phytosanitary products are preparations and materials that contain active and important substances in order to protect plants from the effects of harmful organisms or inhibit their action. Pesticides consist of solutions or mixtures of active compounds on plants. Phytosanitary products are also known by several terms such as: anti-parasitic products for agricultural use, products to combat crop enemies, agricultural pharmaceutical products, plant pharmaceutical products, plant protection products and agricultural products. Pesticides are defined as small particles consisting of an active and toxic part and a secondary part that helps stabilize the pesticide. For pesticides Several types and uses help ensure crops and their quality. But it has undesirable side effects on the environment, and pollutants in general and pesticides in particular lead to harmful effects on the biological cycle in direct and indirect ways. Many scientific studies around the world have highlighted the risks of pollution associated with phytosanitary products on the environment and the ecosystem, Models have been used to assess the risks associated with the use of pesticides, as well as methods and techniques to detect their residues. In order to reduce these risks, we proposed several solutions and alternatives that have proven effective in reducing environmental pollution with phytosanitary products, the most important of which is the manual for using these products, which represents protection for the user and the environment, the use of bio pesticides instead of harmful chemical pesticides, and programs and strategies to reduce the impact on them, and to contribute to this reduction. We offer pest control methods in an environmentally sound manner.
La réduction d’impact environnementale des produits Phytosanitaires
مذكرة ماستر هندسة كيميائيةDes thèses génie chimique
Keywords: المبيدات، البيئة، منتجات الصيدلانية الزراعية، المبيدات الحيوية، منتجات الصحة النباتية; pesticides، ‎‏ ‏‎Phytosanitary products‎‏، ‏‎the environment‎‏، ‏‎biocides، ‏ ‏‎agricultural pharmaceutical products